Selection of heat tolerant donor lines in indian mustard (Brassica Juncea L.) (Bangladesh Journal of Botany, 2023)
Heat stress during the post anthesis (seed filling) stage negatively influences the movement of photosynthates to the developing sinks and, thus lowering the seed yield in Indian mustard [Brassica juncea (L.) Czern & Coss].  The present studywas conducted with the objective to unravel the variability for terminal heat stress (THS) in a fixed diversitygenetic stock of 500 lines of Indian mustard. Germplasm stock exhibited huge variability for seed yield and its contributing traits with variable levels of yield reduction under late sown conditions. The per se yield based computed heat stress susceptibility index (HSI) ranged from 32.3 (highly THS susceptible) to -1.15 (THS tolerant). Based on yield reduction due to THS, 500 test genotypes were grouped into 10 classes and genotypes from each class wererandomly takento constitute a diverse panel of 96 lines. This panel was evaluated under THS by raising crop underpoly-tunnels during reproductive phase along with same set of 96 genotypes raised under normal field conditions (served as control). Based on agronomic advantage and HSI for economic traits, 23 heat tolerant donor lines were selected for utilization in commercial breeding programme. Bangladesh J. Bot. 52(4): 1007-1013, 2023 (December)